Bagaimana E-book â€œChemistry Challengeâ€ Mempengaruhi Profil Literasi Bahan Kimia? Kajian untuk Menguji Efektivitas Media Pembelajaran - Faiz Ilham Pratama; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
The appropriate utilization of media can greatly impact one's chemical literacy. A prior study involved the development of an e-book called "Chemistry Challenge," which is specifically in chemical equilibrium. This research aims to evaluate the chemical literacy profile of students who have utilized the "Chemistry Challenge" e-book and determine if there are significant differences between those who have used it and those who have not. The Chemical Equilibrium Literacy Questionnaire (CELQ) was utilized as an instrument for data collection. The CELQ data was analyzed utilizing ideal criteria assessment to evaluate the chemical literacy profile, and the independent t-test was used to see significant differences. The results of the CELQ show that 82% of students have a chemistry literacy profile in the good and very good categories after using the "Chemistry Challenge" e-book, this result is superior to students who learn using student worksheets. Apart from that, statistically, there are significant differences between the two groups of students. Therefore, the use of the "Chemistry Challenge" e-book has a positive effect on students' chemical literacy profiles.